KEPUASAN STAKEHOLDERS TERHADAP LULUSAN PRODI KI/ MPI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - A Achruh; Ilyas Ismail; Ridwan Idris (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This study will discuss stakeholder’s satisfaction with the performance of KI/MPI graduates at the Tarbiyah and Teaching Faculty of UIN Alauddin Makassar. Then try to find out the criteria that stakeholders want. This research is quantitative descriptive. The population of this study were MPI program graduates who were in the district. Jeneponto, Kab. Selayar, Kab. Pinrang, Makassar City, Kab. Barru, and the City of Parepare. The technique used was a questionnaire with a Likert scale instrument. The analysis used is descriptive quantitative. The criteria that the stakeholders want for graduates of the Islamic Education Management Study Program (MPI), Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar are: (1) responsibility; (2) productive; (3) target orientation or results; (4) high motivation; (5) patient and work hard; (6) think and act positively; and (7) maintain relationships with peers.